Некоторые аспекты весенней миграции воробьиных на косе Бирючий остров - Попенко, В.М.; Дядичева, Е.А. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 1998)
Представлены данные по видовому составу, возрастному распределению, динамике численности и главным направлениям миграции воробьиных на косе Бирючий остров. Исследования проводились в апреле 1995 с помощью визуальных наблюдений. Также проводился отлов паутинными сетями. Наведено дані щодо видового складу, вікового розподілу, динаміки чисельності і головних напрямків міграції горобцевих на косі Бірючий острів. Дослідження проводилися в квітні 1995 року за допомогою візуальних спостережень. Також проводився вилов павутиновими сітками. Data on the species composition, age distribution, number dynamics and main directions of migration of passerines on the spit of Biryuchiy Island, collected in April 1995 by means of visual observations and mist-netting, are presented. Spring migration along the spit was not intensive within the research period; the peak of migration was found to be on 19 April. Data of mist-netting showed that a great proportion of juveniles was passing. They made on average 82.6% of the total catch that is higher than in Crimea peninsula at the same time. Obviously, in spring the spits of the north-western Azov Sea coast are less important stop-over sites for migrating passerines than in autum. They are used mainly by juveniles, including those which had lost their general route.